The role of community health workers in palliative care in a rural subdistrict in South Africa - Elza M. van Heerden; Louis S. Jenkins (AOSIS, 2022)
Background: Effective palliative care is an urgent humanitarian need, particularly in less developed countries, including South Africa (SA). People can be palliated within their communities, motivating the integration of palliative care into primary healthcare systems. While community health workers (CHWs) play a vital role in health coverage at the primary care level, literature on their roles in palliation is limited. Aim: To explore the roles of CHWs in palliative care delivery in a rural subdistrict in SA. Setting: This study was conducted in the George subdistrict of the Western Cape province, SA. Methods: A descriptive qualitative study explored the perceptions of a wide range of stakeholders (n = 39) of CHWs' roles in palliative care. Data were collected via semistructured interviews and focus group discussions and analysed thematically. Results: Patients experienced severe biopsychosocial symptoms and needed home-based palliation. While CHWs identified and referred patients, their main responsibilities were health promotion and disease prevention. Palliation was primarily a registered nurse's function. Community health workers were conflicted by their limited ability to deliver basic palliative care to patients. Conclusion: While there is a definite need for community-based palliative care, the optimal structure of such a service and the roles of CHWs therein are uncertain. Future research should explore the home-based palliation needs of patients in similar contexts and the service design best suited to address these needs within the primary healthcare domain. Contribution: This study illustrates the influence of individual and system-related factors on CHWs' roles in palliative care. It can inform service design to optimise CHWs' contribution to palliation within primary health care.